1995
DOI: 10.1152/jappl.1995.78.5.1772
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic threshold and respiratory compensation in pregnant women

Abstract: In an effort to explore why CO2 output (VCO2) at peak exercise is lower during pregnancy than postpartum despite little change in the peak O2 uptake (VO2), we determined the VCO2/VO2 relationship during rapidly incremental exercise and estimated the anaerobic threshold (AT) and the respiratory compensation (RC) point. We measured heart rate, VO2, VCO2, and minute ventilation (VE) at rest and during cycle exercise tests with rapidly increasing exercise intensities until maximal effort in 33 volunteers at 16-, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…It is well documented that HR is augmented both at rest and during submaximal exercise and that these differences in HR compared with the nonpregnant state decrease with increasing exercise intensity (21). Finally, although the effects of pregnancy on maximal aerobic power are controversial (29), existing studies indicate that T vent is not changed (16,30). Thus our results are consistent with and confirm the results of earlier studies of the effects of human pregnancy on generalized metabolic and cardiorespiratory responses to exercise.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is well documented that HR is augmented both at rest and during submaximal exercise and that these differences in HR compared with the nonpregnant state decrease with increasing exercise intensity (21). Finally, although the effects of pregnancy on maximal aerobic power are controversial (29), existing studies indicate that T vent is not changed (16,30). Thus our results are consistent with and confirm the results of earlier studies of the effects of human pregnancy on generalized metabolic and cardiorespiratory responses to exercise.…”
Section: Discussionsupporting
confidence: 92%
“…§ Significant change within group from cycling at 70% ventilatory threshold (T vent ) to cycling at 110% T vent , P Ͻ 0.05. both at rest and during submaximal exercise relative to the nonpregnant state (21,22). RER does not appear to be altered at work rates below the onset of blood lactic acid accumulation (16,29). It is well documented that HR is augmented both at rest and during submaximal exercise and that these differences in HR compared with the nonpregnant state decrease with increasing exercise intensity (21).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The women in our study reported mild‐to‐moderate persistent activity‐related breathlessness, as evidenced by a ∼3.5 unit decrease in the BDI focal score from PP to TM 3 . Consistent with the results of previous studies (Sady et al 1989; Lotgering et al 1995), however, aerobic working capacity was well preserved in late gestation: women exercised to at least 100% of their predicted maximum work rate and in TM 3 and PP, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Protocols that have been reported are remarkably similar. After a 2-to 4-min warm-up during which the patient pedals against little or no resistance, resistance is increased by 20-30 W/ min to volitional fatigue [34,[36][37][38][39][40]. Upright leg cycle ergometry protocols have been used successfully from 16 to 35 weeks of gestation to 12 weeks postpartum.…”
Section: Maximal Exercise Testsmentioning
confidence: 99%